The factors affecting patient aggression scale: psychometric testing of a new tool - Lepiešová, Martina; Farský, Ivan; Zanovitová, Mária; Čáp, Juraj; Žiaková, Katarína; Kalánková, Dominika (Central European Journal of Nursing and Midwifery, 2021)
Aim: To report the development and psychometric testing of the Factors Affecting Patient Aggression Scale (the FAPAS), a new attitude scale constructed to measure nurses' perception of miscellaneous factors in terms of their potential to increase the risk of patient aggression against nurses. Design: A cross-sectional study. Methods: The study was conducted according to the STROBE checklist. Data were collected using the FAPAS between November 2014 and May 2015. Registered nurses (n = 1,220) from nine teaching hospitals across Slovakia were included in the study. Construct validity and reliability of the instrument were tested using SPSS 18.0. Results: Resulting from the factor analysis, a six-factor structure was revealed. Six subscales representing specific groups of factors affecting patient aggression against nurses can be conditioned by Gender aspects, Situations of physical and emotional distress of a patient, Nurse-related factors, Factors of nursing shift organization, Patient-related factors, Factors of the nursing workplace environment. The Cronbach's alpha of the instrument was 0.91, ranging from 0.63 to 0.88 for subscales. Conclusion: Based on psychometric testing in the Slovak sociocultural context, the FAPAS showed acceptable reliability and construct validity and thus is considered a promising instrument for measuring nurses' perception of miscellaneous factors of patient aggression.
Keywords: nebezpečné chování; Aggression; Nurse-Patient Relations; lidé; Psychometrics; agrese; Nurses; psychometrie; Dangerous Behavior; Patients; vztahy mezi ošetřovatelkou a pacientem; zdravotní sestry; pacienti; Humans